Tradisi Menyambut Bulan Ramadhan: Malam Punggahan dan Membersihkan Makam di Desa Kaana Pulau Enggano - Rizki Aditya Kumara; Sri Sugita Styo Wati; Seli Nurhidayah (Yayasan Darusssalam Bengkulu, 2025)
This study examines the traditions of the Kaana Village community, Enggano Island, in welcoming the holy month of Ramadan through two main activities, namely the night of punggahan and cleaning the graves of ancestors. This study uses a qualitative approach with a documentation study method, obtained from field notes, documentation of activities, and the author's direct experience during the Real Work Lecture (KKN) in the village. The tradition of the night of punggahan is carried out as a form of spiritual preparation for Ramadan, which is marked by praying together, eating together, and forgiving each other among residents. Meanwhile, the tradition of cleaning the graves is carried out through mutual cooperation as a form of respect for ancestors and to strengthen family values ​​and spirituality. The results of the study show that both traditions play an important role in strengthening the cultural identity and social solidarity of the Kaana Village community. This tradition also reflects a harmonious blend of Islamic teachings and local wisdom that continues to be maintained to this day.